Pentingnya Kualitas Pelayanan Dalam Meningkatkan Kepuasan Pasien Puskesmas - Risman, Risman (Eko dan Bisnis: Riau Economic and Business Review, 2023)
This research was carried out at the Koto Kampar Hulu Community Health Center. The aim of this research is to determine the importance of service quality in increasing patient satisfaction at the Koto Kampar Hulu Community Health Center. In analyzing the data obtained from the research object using quantitative analysis and the number of respondents was 98 people, based on the discussion using simple linear regression, the resulting regression equation was Y=14.095+0.680 X. This means that the value of a is 14.095, this value shows that When the service quality variable (variable patient satisfaction (variable Y) will increase by 0.680 units. The t-count value is 10.611. So when compared to the t-table at significant a = 5%, namely 1.98498, it can be seen that the t-count is greater than the t-table (10.661 > 1.98498). Thus it can be concluded that variable X or the service quality variable has a positive and significant influence on patient satisfaction at the Koto Kampar Hulu Community Health Center. This means that the hypothesis answer for this research is Ha accepted and Ho rejected. The coefficient of determination (R Square) value of 0.540 or 54.0% shows that the service quality variable contributes to the patient satisfaction variable by 54.0% while the remainder is 46. 0% (100% - 54.0%) was influenced by other factors not examined in this study